The position of the Saudi system of office services - Ayachi, Warda Belqasim (Journal of Economic, Administrative and Legal Sciences, 2018)
The new challenges that have emerged in the field of libraries and information led authorities concerned to the need to deal with it optimally, which allows the provision of information services to the beneficiaries of the library, including helping to develop scientific research and increase the culture of the community and because of the crucial role played by libraries as an area fertile ground for the production and circulation of information and dissemination, necessitated the need to highlight the importance of the legal systems that control and regulate, and coordinate procedures and information services and institutions of libraries and information centers, what are the legal mechanisms provided by the Saudi regime and to stimulate the development of services in the libraries at the national level? Among the most important recommendations of the study are the following:• Rehabilitation and training of staff in the library to keep abreast of developments in the field of office work.• The university library should adopt a well-thought-out policy based on a rational understanding of the actual needs of the various categories of beneficiaries in relation to the acquisition of library collections, so that it is a rich and integrated collection of different sources of information.• The need to subscribe to the bibliographic databases, in order to enhance the sources of scientific research free of charge.• The Central Library should develop its services and plan to develop new information services gradually according to priorities based on a good knowledge of the needs and needs of the beneficiaries and through its website.
Keywords: library services; the Saudi system to stimulate library service; the Saudi deposit system; King Abdul Aziz Public Library; King Fahd National Library